TRANSLATION OF VERBAL HUMOR IN ENGLISH SUBTITLE OF WARKOP DKI REBORN: JANGKRIK BOSS! Part 1 (2016) - Genta Pertiwi Hayuning Pandawi; Ina Sukaesih (LinguAmerta, 2024)
In the world of translation, there is still a lack of research on how Indonesian jokes are translated into English, especially in the legendary movie Warkop DKI. The objectives of this study are to identify the type of verbal humor based on Long & Graesser (1988), identify the subtitling technique based on Gottlieb (1992), and determine the accuracy and acceptability level of the verbal humor translation based on Nababan et al. (2012). This research uses a qualitative descriptive method. In this study, the data source will be the English subtitle in the Warkop DKI Reborn: Jangkrik Boss! Part 1 (2016) movie. This research conducted content analysis to collect the data and Focus Group Discussion with the rater to asses the level of accuracy and acceptability. This research shows some results. There is a dominating type of verbal humor which is Nonsense, followed by Hostile, Sexual, Social Satire, Demeaning to women, Philosophical, Sick, Scatalogical, and Ethnic. Demeaning to men is not found in this study. For subtitling technique, the most dominating technique is Paraphrase, followed by Transfer, Paraphrase & Deletion, Decimation, Imitation, Resignation, Condensation, Deletion, Paraphrase & Decimation, and Transfer & Imitation. Expansion and Transcription technique are not found. The accuracy aspect of verbal humor translation shows Inaccurate translation in a score of 1.53. Meanwhile, the acceptability aspect shows Acceptable translation in a score of 2.92.